2018
DOI: 10.1177/0040571x18805908
|View full text |Cite
|
Sign up to set email alerts
|

Big data and the Facebook scandal: Issues and responses

Abstract: The recent scandal over the appropriation of users’ data from the Facebook platform serves to surface wider concerns about ‘big data’, relating inter alia to the ways in which personal data are obtained, stored and used for commercial purposes. This article outlines some of the issues involved, and sketches some of the ways in which theologically inspired reflection and action might begin to address those issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…When negative content was increased in users’ feeds, their posts became more negative as a result [ 88 ]. Recently, Facebook was criticized for carrying out such experiments, which can have an impact on mental health, personal decisions and in many cases political election outcomes [ 89 ]. All of this results in users’ skepticism of the platform, contributing to its negative nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When negative content was increased in users’ feeds, their posts became more negative as a result [ 88 ]. Recently, Facebook was criticized for carrying out such experiments, which can have an impact on mental health, personal decisions and in many cases political election outcomes [ 89 ]. All of this results in users’ skepticism of the platform, contributing to its negative nature.…”
Section: Discussionmentioning
confidence: 99%
“…The findings supported the concept of platform-appeal fit. When negative content was increased in users' feeds, their posts became more negative as a result [88]. Recently, Facebook was criticized for carrying out such experiments, which can have an impact on mental health, personal decisions and in many cases political election outcomes [89].…”
Section: Platform Effect On Appeal Effectivenessmentioning
confidence: 99%
“…In parallel with these changes in research practice, high profile cases of data misuse have emerged, exposing research participants to privacy breaches and risk of harm ( Fuller, 2019 ). In response, debate has increased about the role and effectiveness of the Research Ethics Committee (REC) as the chief ethical research oversight mechanism in research, given the specific challenges presented by research with big data ( Ferretti et al, 2020 ; Rennie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Speaking through the "Data Information Knowledge Wisdom (DIKW) Hierarchy" by Cooley (1987), Zeleny (1987) and Ackoff (1989), this widens the gap between a small, highly skilled scientific community reaching knowledge and wisdom about data, and the majority of the population lacking the skills and appropriate platforms to even access the data. In addition, immature ethical and legal guidelines complicate the use of original data outside research (Heikinheimo et al, 2020;Fuller, 2019). While research in urban planning has consistently identified a "data gap" (Voskamp et al, 2018) we identify a particular platform gap in urban planning.…”
Section: Introductionmentioning
confidence: 89%